(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Gram-negative isolates with multiple beta-lactamase enzymes often possess gene determinants for resistance to non-beta-lactam antibiotics. The present study evaluates the in-vitro efficacy of β lactam/non-β lactam antimicrobials against extended-spectrum beta-lactamase (ESBL) genotypes from wound infection. The minimum inhibitory concentrations (MICs) of antimicrobials against 38 Enterobacteriaceae isolates from wound infection were determined by Vitek 2 ID/AST cards. ESBL genotypes: SHV, TEM, CTX-M, and OXA-10/11 genes were detected by real-time PCR. A correlation was found between ESBL genotypes and its resistance to imipenem and amoxycillin clavulanate that is statistically significant (p-value < 0.005). No statistically significant finding was noted among ESBL genotypes which showed resistance to meropenem, amikacin, gentamicin, piperacillin-tazobactam, ciprofloxacin and cotrimoxazole (p-value > 0.005). About 85.19% ESBL genotypes showed imipenem and meropenem susceptibility (MIC:- 0.025–1 μg) and to amikacin (MIC:≤ 2–16 μg). In 44.44% of ESBL genotypes showed susceptibility to cefepime (MIC: ≤ 2 μg) and 7.41% showed cefepime MIC of 4 to 8 μg (Susceptible Dose-Dependent). The emergence of carbapenem-resistant Enterobacterales have highlighted the need to assess the in-vitro efficacy of non-carbapenem betalactam and non-betalactam therapeutic alternatives to treat ESBL infections. Depending on the MIC of cefepime and susceptibility data of aminoglycosides, cotrimoxazole and fluoroquinolones, these drugs can be considered as carbapenem sparing drug as well as for non bacteremic ESBL therapy.